Have the Constitutions of the New Latin American constitutionalism succeeded? - Martínez Dalmau, Rubén (2019)
Since the nineties of the last century Latin America is experiencing a cycle of democratic constituent processes that is usually known in the doctrine as new constitutionalism. Decades after its approval, it is necessary to analyze critically the effects of the new constitutionalism, which wanted to improve the social situation, democratize politics and transform the State. The article raises four questions: 1. Have the Constitutions served to improve the welfare conditions of citizens? 2. Has it been possible to limit the power of the constituted organs? 3. Has inequality and poverty decreased? 4. Has the civil rights situation improved? If we are able to respond affirmatively to the previous questions, we could speak of popular constitutionalism; otherwise, we could only speak of populist constitutionalism.